Cannabidiol as a modulator of α7 nicotinic receptors - Chrestia, Juan Facundo (2022)
Cannabidiol (CBD), an important terpenoid compound from marijuana with no psychoactive effects, has become of great pharmaceutical interest for several health conditions. As CBD is a multitarget drug, there is a need to establish the molecular mechanisms by which CBD may exert therapeutic as well as adverse effects. The α7 nicotinic acetylcholine receptor (α7 nAChR) is a cation-permeable ACh-gated channel present in the nervous system and in non-neuronal cells. It is involved in different pathological conditions, including neurological and neurodegenerative disorders, inflammation, and cancer. By high-resolution single-channel recordings and confocal microscopy, we here reveal how CBD modulates α7 nAChR ionotropic and metabotropic functions. CBD leads to a profound concentration-dependent decrease of α7 nAChR single-channel activity with an IC50 in the sub-micromolar range. The inhibition of α7 nAChR activity, which takes place through a membrane pathway, is neither mediated by receptor phosphorylation nor overcome by positive allosteric modulators and is compatible with CBD stabilization of resting or desensitized α7 nAChR conformational states. CBD modulation is complex as it also leads to the later appearance of atypical, low-frequency α7 nAChR channel openings. At the cellular level, CBD inhibits the increase in intracellular calcium triggered by α7 nAChR activation, thus decreasing cell calcium responses. The modulation of α7 nAChR is of pharmacological relevance and should be considered in the evaluation of CBD potential therapeutic uses. Thus, our study provides novel molecular information of CBD multiple actions and targets, which is required to set the basis for prospective applications in human health.